Exploring the concept and management strategies of caring stress among clinical nurses: a scoping review - Goudarzian, Amir Hossein; Nikbakht Nasrabadi, Alireza; Sharif-Nia, Hamid; Farhadi, Bahar; Navab, Elham (Frontiers in Psychiatry, 2024)
Objective The concept of caring stress and its specific management has received less attention than other dimensions of stress in nurses. Therefore, to clarify the concept of caring stress, a scoping review study was designed. This scoping review aimed to investigate the concept of caring stress among clinical nurses and examine the strategies used for its management. Methods This review employed a scoping review methodology to comprehensively map the essential concepts and attributes of the phenomenon by drawing on a wide range of sources. International databases including PubMed, Scopus, Web of Science, Google Scholar, and Scientific Information Database (SID) were searched to gather relevant studies published until October 1, 2023. MESH terms included “caring stress”, “care”, “stress”, “nurse”, and “stress management” were used. Two reviewers independently collected data from full-text papers, ensuring that each paper underwent assessment by at least two reviewers. Results Out of 104,094 articles initially searched, 22 articles were included in this study. High workloads, transmitting the infection, stressful thoughts, stressful emotions, and stressful communications were the significant concepts and factors of caring stress among nurses. Also, rest breaks during patient care shifts, playing music in the ward, and denial of critical situations were examples of positive and negative coping and management ways to reduce caring stress. Conclusion Effective stress management strategies can lead to better patient care and safety. Stressed nurses are more likely to make errors or become less vigilant in their duties, impacting patient outcomes. By addressing caring stress, clinical practice can prioritize patient well-being. Further research is required to delve deeper into this critical issue concerning nurses in the future.